‘The trees do not belong to Chief Maranke but to the Native Reserves Trust’: The politics of timber resource exploitation in African reserves, colonial Zimbabwe, 1924–1948 (Historia, 2021)
Contextualised within a settler state characterised by racial discrimination and unequal access to natural resources, this article examines the ideological, environmental and economic considerations surrounding the formation of the Native Reserves Trust (NRT) and the role it played in the exploitation of timber resources in the African reserves of Southern Rhodesia (now Zimbabwe). Cognisant of the fact that the colonial state set aside marginal and less productive reserves for the Africans, the paper uses the NRT as a lens to view the process by which the settler society penetrated African reserves and exploited timber resources that were needed for the white-owned enterprises, while at the same time, Africans were barred from exploiting the same resources in European domains. The study further discusses the significance of timber in the African reserves, analyses the role of the NRT in regulating timber exploitation processes and the relations between the state, timber concessionaire companies and the African communities. Lastly, it assesses the extent to which timber exploitation contributed to environmental destruction, and how this prompted a policy shift, leading to the implementation of state-initiated afforestation programmes in these reserves and how these re-shaped state-African relations. On the whole, we note that the exploitation of timber resources in African areas replicated the larger colonial policy that favoured whites at the expense of Africans.
Keywords: Native Reserves Trust; African reserves; timber; afforestation; Southern Rhodesia; colonial Zimbabwe; natural resources